Interference of tumor necrosis factor inhibitor treatments on soluble tumor necrosis factor receptor 2 levels in rheumatoid arthritis - Nicole Yang; Jie Huang; Michelle Frits; Christine Iannaccone; Michael E. Weinblatt; Nader Rifai; Nancy Shadick; Gary Bradwin; Katherine P. Liao (Practical Laboratory Medicine, 2019)
Objective: Soluble Tumor Necrosis Factor Receptor II (sTNFR2) is used as a biomarker to study cardiovascular disease (CVD) in diverse populations. TNF inhibitors (TNFi's) are a common treatment for inflammatory conditions. The objective of this study was to examine whether TNFi use impacts measured sTNFR2 levels. Methods: We studied blood samples from a cohort of RA patients with clinical data and high sensitivity-C-reactive protein (hsCRP) measurements. To assess for interference, we tested the entire cohort for the expected positive correlation between sTNFR2 and TNFi using Pearson correlations. We then performed Pearson correlations between sTNFR2 and TNFi and sequentially removed subjects on adalimumab, etanercept, and infliximab; if interference was occurring, no correlation would be observed between hsCRP and sTNFR2, and correlation would be restored by removing subjects on the treatment causing the interference. Results: We studied 190 subjects, 84.2% female, 73.4% anti-CCP positive. All subjects with sTNFR2 level exceeding measurable level were on etanercept. The expected positive correlation between hsCRP and sTNFR2 was not observed when assessing the entire cohort, r = 0.05, p = 0.51. However, the expected correlation was restored only after excluding subjects on etanercept, r = 0.46, p < 0.0001, and not adalimumab or infliximab. ELISA for sTNFR2 was performed using etanercept only and demonstrated direct binding to sTNFR2. Conclusions: Our data identified interference between etanercept and the TNFR2 assay. Of the TNFi's, only etanercept has a TNF-binding domain modeled after TNFR2. These data should be considered when designing studies using sTNFR2 in populations where etanercept is a treatment option. Keywords: Rheumatoid arthritis, Cardiovascular, Inflammation, Tumor necrosis factor inhibitor (TNFi), High sensitivity C-reactive protein (hsCRP), Biomarker